A constrained extremum‐seeking control approach. (9th October 2014) - Guay, Martin; Moshksar, Ehsan; Dochain, Denis
Summary This paper proposes an extremum‐seeking control approach for a class of uncertain nonlinear dynamical systems subject to constraints. It is assumed that the objective function along with the constraints are available for measurement. The contribution of the paper is to formulate the extremum‐seeking problem as a time‐varying estimation problem. The constraints are enforced by using an interior point strategy that preserves feasibility of the systems' trajectories. Simulation examples are used to illustrate the effectiveness of the proposed technique. Copyright © 2014 John Wiley & Sons, Ltd.